Novel Zinc(II) Phthalocyanine Dyes for Color Photoresists - Wang, Wanying; Yao, Qichao; Xu, Runfeng; Wang, Ankang; Chen, Pengzhong; Peng, Xiaojun (Synlett, 2023)
Color photoresists are the key materials for the fabrication of color filters (CFs). Organic dyes offer a promising alternative to the conventional pigment-based system to make CFs with higher resolution. However, the stability of dye molecules is an urgent problem to be solved. Herein, we designed and synthesized a series of highly stable zinc phthalocyanine dyes containing polymerizable acrylamide groups. Upon light exposure, dense and insoluble network structures were formed in the prepared CFs, which increase the thermal stability and anti-migration capacity of these dyes.
Keywords: color photoresist; dye-based color filter; zinc phthalocyanine; functional dye; high stability